2010
DOI: 10.1097/tme.0b013e3181fd4f7d
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prehospital Blood Collection on Time to Laboratory Test Results and Emergency Department Length of Stay

Abstract: Introduction: The purpose of this prospective study was to determine the impact of obtaining blood specimens in the prehospital setting versus drawing specimens in-hospital. Variables examined were length of time from arrival to laboratory result availability; specimen quality; and emergency department length of stay. Methods: A total of 101 patients were enrolled in the study and assigned to either prehospital group (n = 58) or the in-hospital group (n = 43). Clinical laboratory personnel were blinded to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…[15,16] Waiting for laboratory results is frequently described as a cause for increased EDLOS and crowding. [13,17,18] In our study, the improvement in the efficiency of laboratory testing was reflected in a shorter EDLOS when adjusted for other factors. In our regression model concerning EDLOS, 26% of the variation was explained by prehospital blood draw, age, a second troponin draw, and a radiology request, suggesting that other, possibly important, contributors to EDLOS were not measured in this study.…”
Section: Controls In Analyses N=406supporting
confidence: 47%
See 2 more Smart Citations
“…[15,16] Waiting for laboratory results is frequently described as a cause for increased EDLOS and crowding. [13,17,18] In our study, the improvement in the efficiency of laboratory testing was reflected in a shorter EDLOS when adjusted for other factors. In our regression model concerning EDLOS, 26% of the variation was explained by prehospital blood draw, age, a second troponin draw, and a radiology request, suggesting that other, possibly important, contributors to EDLOS were not measured in this study.…”
Section: Controls In Analyses N=406supporting
confidence: 47%
“…A study analysing 101 patients demonstrated door-to-result times for serum chemistry studies in cases being 28 min faster than controls (P<0.02). [13] A 29-minute decrease in LOS was observed which did not reach statistical significance. In a study including 400 patients, the authors concluded that the practice of prehospital blood draws by EMS in the field should be supported, based on no differences in redraw rates and a non-significant decrease in median LOS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation